Análise do aproveitamento energético de resíduos sólidos urbanos para a produção de combustível derivado de resíduos: um estudo de caso no Espírito Santo, Brasil - Bianchi, Karla Silva Bisi (2023)
The excessive generation and inadequate disposal of urban waste is one of the concerns of society and public authorities. The need to reduce emission of polluting gases, in addition to the generation of new renewable energy sources, makes the energy use of waste an alternative to this problem. One of the available options is the Refuse Derived Fuel (RDF) that can be obtained from hazardous and non-hazardous waste, by making use of Municipal Solid Waste (MSW). The RDF can be used in several industrial sectors, due to its high calorific value and its moderate environmental impacts. On the other hand, cement industries are characterized by its high energy consumption and uses of highly polluting fossil fuels. RDF stands out as a potential substitute for fossil fuels used in this sector. Through co-processing technology, the RDF has the potential to mitigate environmental impacts generated by cement industries and incorporate their waste into the cement clinker. Although Brazil has instruments that encourage energy recovery from waste as a form of treatment, such as the Brazilian Solid Waste Policy (BSWP), the country is still moving slowly in this direction. This dissertation analyzes the economic viability of a plant to convert MSW into RDF, aiming fossil fuel substitution in cement industries located in Espírito Santo (ES). For this, economic engineering tools will be used, such as the project's cash flow, Net Present Value (NPV), Internal Rate of Return (IRR) and Payback, besides the comparison between commercialization values of RDF and coke of petroleum, for substitution of petroleum coke in cement industries. However, some variables, such as: per capita waste generation, transport costs, RDF calorific value, technological efficiency, capital costs, operating costs, petroleum coke substitution rate, petroleum coke and RDF prices influence the economic parameters. For this, a sensitivity analysis will be carried out, based on information collected and the calculated data, to measure uncertainties of important parameters in economic indicators. To analyze the project risks, a Monte Carlo simulation will be employed, measuring the combined effect of these variables on the economic performance for the process integration through their impact on NPV. It is expected that this study provides the feasibility assessment of using MSW generated in the state of Espírito Santo state for the production of RDF and its replacement of fossil fuels in cement industries, filling the gap in the Brazilian literature.